Hillforts and the durotriges : a geophysical survey of Iron Age Dorset - Stewart, Dave (Archaeopress Publishing Ltd, 2017)
This volume sets out the results of a detailed programme of non-intrusive geophysical survey conducted across hillforts of Dorset (UK), generating detailed subsurface maps of archaeological features, in the hope of better resolving the phasing, form and internal structure of these iconic sites.